Developing Students’ Character through Tauhid-Based Learning: An Analytical Study of the Implementation of Kitab As-Sa’adah - Riky Aldino Alif; Saifulah Saifulah; Ahmad Marzuki; M. Anang Sholikhudin (Al-Qalam Institue, 2026)
This study aims to examine how students’ character is formed through tauhid learning using Kitab As-Sa’adah. Employing a qualitative approach with a field research design, the study collected data through observations, interviews, and documentation involving teachers, school leaders, and students to gain an in-depth understanding of the learning process and value internalization. The findings indicate that tauhid learning is implemented systematically through structured stages and supported by diverse teaching methods, including lectures, discussions, and habituation practices. Internalization of tauhid values occurs through religious activities, teacher role modeling, and integration into daily behavior, fostering students’ religious, disciplined, and responsible character. Key supporting factors include a consistent religious program, an immersive learning environment, and active teacher involvement, whereas challenges arise from students’ difficulty with classical terminology, varied learning abilities, and external influences such as social and media exposure. The study highlights that tauhid-based instruction using Kitab As-Sa’adah effectively enhances both students’ understanding of faith and the holistic development of their character.